PENYUSUNAN NERACA AWAL AWAL PEMERINTAH DESA DI DESA TEGOWANU KULON KABUPATEN GROBOGAN - Oktavie Fresiliasari; Suhardjo, Yohanes (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2025)
In order to prepare the initial balance sheet, the village government must attach a report on village-owned assets to the LRAPBDesa. This report of village-owned assets is similar to a balance sheet. The purpose of this PKM activity means that the Tegowanu Kulon Village Government, Tegowanu Sub-district, Grobogan Regency will prepare the Tegowanu Kulon Village Government Balance Sheet for the first time. So that the preparation of the initial balance sheet can be carried out smoothly and fulfils the provisions of the applicable laws and regulations. To determine the success of the training activities for the preparation of the initial Village Government Balance Sheet for the Tegowanu Kulon Village Government apparatus, Tegowanu Subdistrict, Grobogan Regency, an evaluation was carried out, namely using a pre-test and post-test for training participants. The training is called successful if the post test score is higher than the pre test score with a minimum score of 80. The results of the discussion in this PKM activity are the presentation of material regarding the preparation of the Initial Village Government Balance Sheet, participants are given an understanding of the village asset inventory, historical cost-based recognition method, fair value-based valuation method, form and accounts of the Village Government Balance Sheet. The presentation also explained the practice of accounting for village assets. The presentation of the material confirmed that the practice of village financial reporting applies the accrual basis. During the activity, participants followed the activity until it was completed. Participants also actively asked questions related to the material presented by the resource person.